2011
DOI: 10.2139/ssrn.1866766
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Country-of-Origin Characteristics for Foreign Direct Investment and Technical Cooperation in Post-Reform India

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 47 publications
(18 reference statements)
3
5
0
Order By: Relevance
“…While genuine investors locate in regions supplied with educated, productive and skilled labor (see columns 1 and 3 in Table 4) round-trip investors choose locations with low costs and low skills, suggesting their greater involvement in vertical projects that are not skill-intensive (columns 9 and 10 in Table 6). The same result is reported by Dreher et al (2013) for India, where non-resident Indians, roughly comparable to round-trip Russian investors, are less reliant on skilled local labor than FDI from other sources. In addition, governor change in the regions significantly discourages round-trip investors, a factor which is completely irrelevant for genuine investors.…”
Section: (C) Accounting For Round-trip Investorssupporting
confidence: 79%
See 2 more Smart Citations
“…While genuine investors locate in regions supplied with educated, productive and skilled labor (see columns 1 and 3 in Table 4) round-trip investors choose locations with low costs and low skills, suggesting their greater involvement in vertical projects that are not skill-intensive (columns 9 and 10 in Table 6). The same result is reported by Dreher et al (2013) for India, where non-resident Indians, roughly comparable to round-trip Russian investors, are less reliant on skilled local labor than FDI from other sources. In addition, governor change in the regions significantly discourages round-trip investors, a factor which is completely irrelevant for genuine investors.…”
Section: (C) Accounting For Round-trip Investorssupporting
confidence: 79%
“…They can use their experience of operating with underdeveloped institutions and weak governance, thus gaining an advantage over multinationals from developed economies (Cuervo-Cazurra and Genc, 2008). The desire to escape from an environment of higher risk and weaker institutions in the home country may also be a motivation (Dreher et al, 2013). On the other hand, investors from developed countries may be less affected by institutional deficiencies if they have better access to capital or have support from their home governments to protect their property rights (Fan et al, 2009).…”
Section: Literature Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…He also noted that factors such as inflation and lending rates have no relationship to FDI in India. Similarly, Dreher et al (2013) revealed that market size, financial market development, relative endowment of human capital, and previous international experience significantly affect the type of engagement by foreign investors in post-reform India. Hunady and Orviska (2014) further found that lower exchange rate volatility and greater risk diversification opportunities facilitate portfolio flows in India.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, close countries with high economic flows are more likely to share political and legal approaches to policy adjustment, so learning from neighbors seems a feasible choice for these governments (Dreher et al, 2013).…”
Section: Explaining Diffusion Processes When Policies Have Alternativesmentioning
confidence: 99%